The Old Jambal’s Account about Certain Artifacts Preserved in Urga - Krisztina Teleki, (Acta Mongolica, 2014)
Jambal’s account includes the most precious artifacts of Urga created by Öndör gegeen Zanabazar as well as many others he saw or heard about. The majority of the artifacts of Urga’s temples were destroyed or delivered to Russia in and after 1937-1938. Due to the work of the Institute of Sutras and Scripts founded in 1921, which also had a museum (situated in the Winter Palace of the Bogd after 1924) some of the most precious artifacts could be preserved. Many of them are now on exhibits in the Choijin Lama Temple Museum, the Palace Museum of the Bogd Khaan, and the Fine Arts Zanabazar Museum, whilst others are still used as objects of worship such as the ones preserved at Gandan Monastery. The artifacts and other objects mentioned by Jambal are listed below. The list includes the present (presumable or sure) locations of these objects as well, thought further research of their stories and present availabilities are required. N. a. (not available) is used for unknown data